Analisis Kerusakan Jalan Poros Lembang Bori’ Ranteletok-Lempo Kabupaten Toraja Utara - Kalvyn Uda' Batti; Robert Mangontan; Wona Grace Boro (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The development of a region/region is certainly supported by the existence of infrastructure, which maintenance of road conditions needs to be carried out, where roads are an important factor in the life of the community's economic movement and other social activities. This study aims to determine what types, levels and causes of damage occurred to the segment in Lembang Bori' Ranteletok, North Toraja Regency. The method used is primary data collection in the field by measuring each type of damage to be analyzed for density, deduct value, total deduct value, and pavement condition index as well as secondary data in the form of rainfall data. The results of this study obtained types of road damage, namely crocodile skin cracks, roadside cracks, grain release, potholes, and subsidence. Based on the results of the analysis carried out on the 20 road segments studied, the average value of the PCI method pavement condition is 46.80% moderate (fair), with the lowest pavement value occurring in STA 1+800 to 1+900 with poor classification (poor). From the PCI value of each segment based on the decision matrix, the repair time needs to be rehabilitated now. The cause of the road damage is poor drainage conditions causing water to stagnate on the road load. The handling of road damage is by, the method of maintenance and repair of functional damage is the P2, P5 Repair method which has been set in the Road Maintenance Manual and the Deep Patch Method.